The influence of service quality and company reputation on purchase decisions with customer experience as moderators in creative industrial companies - Andarina, Deansha Ghaisani; Kodrat, David Sukardi (MBR (Management and Business Review), 2024)
This research has purpose to determine the effect of service quality and company reputation on purchasing decisions with customer experience as a moderator in a creative industry company at PT. Rangkai Cipta Kreasi. The method used in this research is a quantitative approach. The number of samples used was 65 respondents, taken using purposive sampling technique. The results of the study revealed that service quality and company reputation have a positive effect on purchasing decisions. Customer experience does not act as a moderator of the influence of quality on service quality but strengthens the influence of company reputation on purchasing decisions.